Land Price Modelling with Radial Basis Function (Case Study: Utan Kayu Selatan Village, East Jakarta) - Sawitri Subiyanto; Hana Sugiastu Firdaus; Nahar Dito Utama Giardi (Journal of Applied Geospatial Information, 2021)
The price of land is an important matter that needs to be assessed by stakeholders. The study of land prices has an important role in seeing the stability of the property market. Several factors affect the property business such as accessibility, public facilities and social facilities. Utan Kayu Selatan is the largest village in Matraman Sub-District with an area of ​​1,12 kilometers. The potential of the property business is very tempting for investors to property developers. One of the economic sector developments is Utan Kayu Raya Road, which can increase land prices in the surrounding area. The factors that influence land prices can be analyzed through several approaches such as regression, mass appraisal and other. In this study, the method used in estimating land prices is the Radial Basis Function (RBF), by looking at the relationship between the distance of plot to roads, public facilities and social facilities. Modeling is carried out based on samples determined on ZNT and NJOP land prices. Furthermore, the calculation of the distance is done by using network analysis. As a result, the RMSE value for the NJOP RBF model and the ZNT RBF model is IDR 1.179.839 and IDR 2.972.345. Meanwhile, the CoV values ​​for both models were 6.2% and 6%. In the comparison of ZNT price predictions with market prices, the highest difference is IDR 13.119.915 and the lowest difference is IDR 537.009. While on the NJOP price prediction, the highest difference is IDR 15.797.583 and the lowest difference is IDR 291.270.